Effects of green tea extract on oxidative stress and renal function in diabetic individuals: A randomized, double-blinded, controlled trial. (July 2018) - Vaz, Sáskia Ribeiro; de Amorim, Luiza Moreira Nogueira; de Nascimento, Pamella Vanessa Freitas; Veloso, Valéria Soares Pigozzi; Nogueira, Marina Sayuri; Castro, Inar Alves; Mota, João Felipe; Botelho, Patrícia Borges
Graphical abstract: Highlights: Green tea extract prevented the reduction of superoxide dismutase activity. Green tea did not promote improvement in total antioxidant capacity. 560 mg of polyphenols did not improve renal markers in diabetic individuals. Abstract: The effects of green tea on oxidative stress and renal function in diabetes remains inconclusive. This study aimed to evaluate the effect of green tea extract on oxidative stress and renal function in diabetic individuals. A randomized, double-blinded, controlled clinical trial was developed with 60 diabetic individuals. Patients were assigned to receive green tea extract (two capsules/day, containing 560 mg of polyphenols/each) or cellulose (two capsules/day) for 20 weeks. Glycaemic control and renal function markers, antioxidant enzymes and total antioxidant capacity were analysed. No difference was observed in glycaemic control, renal function, and oxidative stress, except for superoxide dismutase. After 20 weeks, green tea extract maintained this enzyme activity, whereas an expressive reduction in the placebo group was noted (p = 0.014). Green tea extract prevented the reduction of superoxide dismutase activity; however, it was not associated with an improvement in total antioxidant capacity, glycaemic control markers or renal function.